Intersecting burdens: Homophobic victimization, unstable housing, and methamphetamine use in a cohort of men of color who have sex with men. (1st November 2018) - Li, Michael J.; Okafor, Chukwuemeka N.; Gorbach, Pamina M.; Shoptaw, Steve
Highlights: Homophobic victimization was associated with greater severity of methamphetamine use across 24 months. Homophobic victimization was associated with greater duration of unstable housing across 24 months. Unstable housing partially explained the association between HV and methamphetamine use. Abstract: Background: Men who have sex with men with histories of homophobic victimization bear heightened risk of unstable housing and methamphetamine use. However, it is unclear whether unstable housing explains the link between homophobic victimization and methamphetamine use in this group. The present study aims to test associations between homophobic victimization, unstable housing, and recent methamphetamine use across 24 months in a cohort of men of color who have sex with men (MoCSM). Methods: Our analysis stems from data of 1342 person-visits from 401 MoCSM participating in an ongoing cohort study. We performed a lagged multilevel negative binominal regression to test the association between past homophobic victimization and recent unstable housing, and a lagged multilevel ordered logistic regression to test the association between past homophobic victimization recent methamphetamine use. We then performed a path analysis to test whether recent unstable housing mediates the association between past homophobic victimization and recent methamphetamine use. Results: Findings showed homophobic victimization associated significantly with increased odds of unstable housing (IRR = 1.70, 95% CI [1.35, 2.14], p < 0.001) and recent methamphetamine use (OR = 1.40, 95% CI [1.15, 1.71], p = 0.001). Mediation analysis indicated that past homophobic victimization was indirectly associated with recent methamphetamine use via unstable housing (OR = 1.06 (95% CI [1.01, 1.11], p = 0.010). Conclusion: Our findings suggest that homophobic victimization and unstable housing should be addressed alongside treatment and prevention of methamphetamine use in MoCSM.